Promoting MSME Financing Decisions The Influence of Financial Behavior and the Role of Risk Taking Behavior - Abdul Syukur; Amalia Nur Chasanah; Fery Riyanto (Faculty of Economics and Business Universitas Dian Nuswantoro, 2026)
This study aims to examine the effect of financial behavior on credit decision making among MSME owners in Central Java and to investigate the moderating role of risk-taking behavior. A quantitative approach was employed involving 185 MSME owners selected through purposive sampling. Data were collected using questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that financial behavior has a positive and significant effect on credit decision making. This finding suggests that MSME owners with better financial behavior are more likely to make rational and effective credit decisions. However, risk-taking behavior does not moderate the relationship between financial behavior and credit decision making. The findings highlight that the quality of credit decisions is primarily influenced by financial management capabilities rather than the willingness to take business risks. Penelitian ini bertujuan untuk menganalisis pengaruh financial behavior terhadap credit decision making pada pelaku UMKM di Jawa Tengah serta menguji peran risk taking behavior sebagai variabel moderasi. Penelitian menggunakan pendekatan kuantitatif dengan melibatkan 185 pemilik atau pengelola UMKM yang dipilih melalui teknik purposive sampling. Data dikumpulkan menggunakan kuesioner dan dianalisis dengan Partial Least Squares Structural Equation Modeling (PLS-SEM). Hasil penelitian menunjukkan bahwa financial behavior berpengaruh positif dan signifikan terhadap credit decision making. Temuan ini mengindikasikan bahwa pelaku UMKM yang memiliki perilaku keuangan yang baik cenderung mampu mengambil keputusan kredit yang lebih rasional dan berkualitas. Sementara itu, risk taking behavior tidak terbukti memoderasi hubungan antara financial behavior dan credit decision making. Hasil penelitian menegaskan bahwa kualitas keputusan kredit lebih dipengaruhi oleh kemampuan pengelolaan keuangan dibandingkan keberanian dalam menghadapi risiko usaha.